117 things you should f*#king know about your world - Parsons, Paul, 1971- (Running Press, 2019)
From pinpointing the exact worst time to be alive in human history, to learning what makes you a procrastinator or a go-getter, to the very key to a happy sex life, and so much more, this is the science book that only the world's leading source of crazy-but-true stories could produce.